Sustaining the Mutqin Qur'an Memorization Tradition via the Talaqqi Method - Hilyah Ashoumi; Muhammad Zarkasyi Mahfudh; M Aliyul Wafa (SCHOOLAR: Social and Literature Study in Education, 2025)
The purpose of this study is to find out how the application of the Talaqqi method improves memorization at the Putra Roudhotul Tahfidzil Qur'an Islamic Boarding School. This study uses qualitative research and a case study approach. Data collection using observation, interviews, and documentation. Interviews were conducted with 5 informants. Data analysis techniques are done through data reduction, data presentation, then concluding. Checking the validity of the data is done by extending observation, continuous observation, and triangulation. The results of this study include; 1) Learning the Qur'an at the Roudhotul Tahfidzul Qur'an Islamic Boarding School uses the Talaqqi method, technically the students deposit their memorization to the ustadz ba'da maghrib, then the ustadz reads the maqro` memorization that will be memorized by the students and the students listen well, then the students read the maqro` that the ustadz has read bin nadhor. 2) Roudhotul Putra Islamic Boarding School's efforts to maintain the tradition of mutqin Qur'an memorization by forming a Qur'an learning management consisting of Pre tahfidz, and Tahfidz. The evaluation of learning, namely Tasmi`, and the Pre Tahfidz and Tahfidz Exams are held every semester. In dealing with obstacles when students experience broken memories, Roudhotul Tahfidzil Qur`an Putra Islamic Boarding School provides solutions through individual management from ustadz. 3) Students can target memorization achievements; students are accustomed to consistency in murojaah so maintaining the quality of student memorization is prioritized over the quantity of memorization in a period of time.